Pregnancy with a Normal live Foetus and a Partial Molar Placenta - An Extremely Rare Condition - Khanom, R; Khatun, K; Akter, S (Journal of Dhaka Medical College, 2010)
The incidence of a normal live foetus along with a partial molar placenta is extremely rare. Although triploidy is the most frequent association, a foetus with normal karyotype can survive in cases of partial molar pregnancy. A case is reported in the Department of Obstetrics & Gynaecology, Dhaka Medical College Hospital, Dhaka that of partial molar placenta in which a live male baby was delivered at 34 weeks gestation by a 25 years old woman. At the 23rd week, ultrasonographic examination revealed a normal foetus with a huge, multicystic placenta. There were per vaginal bleeding up to the 34th gestational weeks. The patient underwent an emergency caesarean section and delivered a 1.6 kg male baby. The baby was admitted in SCABU. The foetus was normal and no complication was there. Key words: Live foetus with molar pregnancy; emergency caesarean section. DOI: 10.3329/jdmc.v18i1.6313 J Dhaka Med Coll. 2009; 18(1) : 82-84